IMF Staff Papers, Volume 46, No. 1. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1999)
This economic journal contains theoretical and empirical analyses of varous macroeconomic issues. The studies are prepapred by IMF research staff or consultants. Subjects covered inclulde balance of payments and exchange rates, monetary systems and policies, public finances, international trade, economic growth, and some sectoral analyses. The last issue of the year contains an index to the volume. Approximately 200 pages in each issue.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet